Gerda's Character as the Influence of Lili's Transition in The Danish Girl Film - Septi Herlinda (English Department, Faculty of Humanities, Andalas University, 2022)
This research aims to show how Gerda Wegener, as a supporting character in The Danish Girl film could give the biggest contribution into the main character’s transition from Einar Wegener (male) to Lili Elbe (female) through Gerda’s character and personality depicted in the film. This research uses descriptive qualitative method. To support the analysis, the writer uses the theory of the Big Five personality factors, characterization, and altruism. The result of this research shows that Gerda’s character and personality are found to be the main cause of the conflict that occurred in the film, on how the main character, Einar Wegener in overcoming his gender dyphoria to fully transformed into a woman named Lili Elbe. This research discovered that, based on the Big Five personality factors; Gerda’s personality in agreeableness and openness are highly relatable in influencing Lili’s transition. Moreover, Gerda’s behavior in altruism is also found to be the main reason on why she chose to support the main character’s gender transition despite the huge loss upon her. In conclusion, Gerda Wegener as a supporting character played the biggest role in stirring the plot by her influence in supporting Einar Wegener’s gender transition. It also shows that it is possible for someone to be so selfless when it comes to the person they adore. Finally, it gives a new perspective on how significant the role of a supporting characters are in a film based on their character and personality.